2016
DOI: 10.4103/2045-9912.196905
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative aspect of inhaled anesthetic gases against acute brain injury

Abstract: Acute brain injury is a critical and emergent condition in clinical settings, which needs to be addressed urgently. Commonly acute brain injuries include traumatic brain injury, ischemic and hemorrhagic strokes. Oxidative stress is a key contributor to the subsequent injuries and impedes the reparative process after acute brain injury; therefore, facilitating an anti-oxidative approach is important in the care of those diseases. Readiness to deliver and permeability to blood brain barrier are essential for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…These collective findings also confirm critical role of the BBB in maintaining normal brain function. Not surprisingly, Nrf2 has also been reported to mediate preconditioning with hyperbaric oxygen [68] , remote ischemia [7] , and inhaled anesthetic gas [67] . Thus, the engagement of the Nrf2 pathway serves as a generalizable and stereotypical mechanism underlying ischemic tolerance against stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These collective findings also confirm critical role of the BBB in maintaining normal brain function. Not surprisingly, Nrf2 has also been reported to mediate preconditioning with hyperbaric oxygen [68] , remote ischemia [7] , and inhaled anesthetic gas [67] . Thus, the engagement of the Nrf2 pathway serves as a generalizable and stereotypical mechanism underlying ischemic tolerance against stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Following ICH induction, a large number of free radicals were released, and ROS led to membrane lipid peroxidation and protein and DNA oxidative damage [ 51 53 ]. HO-1 protected cells and tissues during oxidative stress as an important member of antioxidant [ 54 56 ]. NQO1 used NADH or NADPH as electron donors to catalyze the reduction of chinone compounds, thereby avoiding the formation of unstable semiquinone compounds [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 protected cells and tissues during oxidative stress as an important member of antioxidant [ 54 56 ]. NQO1 used NADH or NADPH as electron donors to catalyze the reduction of chinone compounds, thereby avoiding the formation of unstable semiquinone compounds [ 56 , 57 ]. In this study, we found that melatonin increased the expressions of HO-1 and NQO1 after ICH, and these results indicated that melatonin can promote antioxidant in brain tissues after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes, such as SOD and CAT, are key ROS scavengers that specifically eliminate superoxide radicals and prevent ROS-induced brain damage during sepsis ( 24 ). A published review summarizes the anti-oxidative aspects of ISO in acute brain injury ( 63 ). HO-1 is a key participant in sepsis ( 27 29 ), and has been reported to hamper oxidative stress during sepsis-induced acute lung injury ( 64 ).…”
Section: Discussionmentioning
confidence: 99%